Health implications of exposure to radiofrequency/microwave energies - Michaelson, S M (1982)
ABSTRACT The rapid development of and the increase in the number and variety of devices that emit microwave/radiofrequency (MW/RF) energies has resulted in a growing interest regarding the potential effects on health of these energies. The frequency ranges considered in this review are: 300 kHz to 300 MHz (radiofrequency) and 300 MHz to 300 GHz (microwaves). Investigations have shown that exposure to certain power densities for several minutes or hours can result in pathophysiological manifestations in laboratory animals. Such effects may or may not be characterised by a measurable rise in temperature, which is a function of thermal regulatory processes and active adaptation by the animal. The end result is either a reversible or irreversible change, depending on the irradiation conditions and the physiological state of the animal. At lower power densities, evidence of pathological changes or physiological alteration is non-existent or equivocal. Much discussion, nevertheless, has taken place on the relative importance of thermal or non-thermal effects of radiofrequency and microwave radiation. Several retrospective studies have been done on human populations exposed or believed to have been exposed to MW/RF energies. Those performed in the US have not shown any relationship of altered morbidity or mortality to MW/RF exposure. Reactions referrable to the central nervous system and cardiovascular effects from exposure of man to microwave energy have been reported mostly in Eastern European publications. Individuals suffering from various ailments or psychological factors may exhibit the same dysfunctions of the central nervous and cardiovascular systems as those reported to result from exposure to MW/RF; thus it is extremely difficult, if not impossible, to rule out other factors in attempting to relate MW/RF exposure to clinical conditions. There is a need to set limits on the amount of exposure to MW/RF energies that individuals can accept with safety. Operative protection standards have apparently provided adequate safety to workers and the general population to permit the use of MW/RF energies without harm or detriment.